2011
DOI: 10.5603/fhc.2011.0008
|View full text |Cite
|
Sign up to set email alerts
|

<i>ICOS</i> gene polymorphisms in B-cell chronic lymphocytic leukemia in the Polish population

Abstract: Abstract:There is strong evidence that altered immunological function entails an increased risk of B-cell chronic lymphocytic leukemia (B-CLL). The main mechanism of an anti-tumor response depends on T-cell activation. Unlike the constitutively expressed CD28, inducible costimulatory molecule (ICOS) is expressed on the T-cell surface after activation. ICOS enhances all the basic T-cell responses to a foreign antigen, namely proliferation, secretion of lymphokines, the upregulation of molecules that mediate cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
(45 reference statements)
2
11
1
Order By: Relevance
“…In our current study, it was found that the allele 'A' of rs1559931 had a protective effect on HCC development in CHB and HBV-associated LC patients. In addition, rs4675379 has been proposed to be associated with the progression of B cell chronic lymphocytic leukaemia, but no relation was found in type 1 diabetes susceptibility or the outcome of kidney transplantation [20,33,38]. Our current data showed that distribution of the rs4675379 CC genotype was different between HBV infection and clearance, but there was no statistical difference found among the GC genotype, GG&GC+CC and C allele.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In our current study, it was found that the allele 'A' of rs1559931 had a protective effect on HCC development in CHB and HBV-associated LC patients. In addition, rs4675379 has been proposed to be associated with the progression of B cell chronic lymphocytic leukaemia, but no relation was found in type 1 diabetes susceptibility or the outcome of kidney transplantation [20,33,38]. Our current data showed that distribution of the rs4675379 CC genotype was different between HBV infection and clearance, but there was no statistical difference found among the GC genotype, GG&GC+CC and C allele.…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, 5'-untranslated region may also function to regulate gene splicing [30,31]. Being a neighbour to CTLA-4, rs10932029 polymorphism has been reported to affect expression of the CTLA-4 isoforms and be associated with sporadic breast cancer and the disease dynamics of B cell chronic lymphocytic leukaemia [19,20]. However, studies on kidney transplantation and malignant melanoma did not show any significant association with rs10932029 polymorphism [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second SNP is rs10932029 T/C (termed ICOS SNP2) located in the intron region. It has been reported that patients with B-cell chronic lymphocytic leukemia who have the C allele show disease worsening [28]. In ICOS SNP2, comparing the T allele and C allele, those who have the C allele demonstrated a significantly increased risk of breast cancer [30].…”
Section: Genotyping Of Snpsmentioning
confidence: 99%
“…The first SNP in ICOS is rs10183087 A/C (termed ICOS SNP1) located in the 3'-UTR, and it is reported that patients with B-cell chronic lymphocytic leukemia who have the AA genotype of this SNP were protected against heavy progression of this disease [28]. Patients with the AA+AC genotype showed a delayed graft function outcome of kidney transplantation [29].…”
Section: Genotyping Of Snpsmentioning
confidence: 99%